ANALISIS AKAD-AKAD PELENGKAP DALAM AKUNTANSI SYARIAH: ANALISIS AKAD-AKAD PELENGKAP DALAM AKUNTANSI SYARIAH - Fahmi, Ilham; Rosyidah, Umu (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
This study aims to analyze the alignment between the legal substance of complementary contracts (kafalah, hawalah, rahn, wakalah, wadi'ah) in muamalah fiqh with their accounting treatment. Using a qualitative legal-normative method, this study comparatively analyzes fiqh literature, DSN-MUI fatwas, and Sharia Financial Accounting Standards Statements (PSAK). The results of the study indicate significant alignment, where Sharia PSAK consistently reflects the nature of contracts such as guarantees and mandates through off-balance sheet recording and service-based revenue recognition. The main implication is the need to expand more substantive qualitative.